OPTIMALISASI PENYELENGGARAN PELAYANAN PUBLIK DALAM MASA PERUBAHAN MELAWAN COVID-19 DI INDONESIA - Diana Setiyo Dewi; Tiur Nurlini Wenang Tobing (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
This study focuses on COVID-19 as a global pandemic that has a negative impact on various government fields. The government made a new online-based policy on public service delivery. Public services before COVID-19 are seen as not optimal, the improvement needs are piling up in line with the delays during the COVID-19 pandemic, it is very necessary to optimize the implementation of good governance, problems we are facing now are the threat of COVID-19 against the deterioration of the country, new policies that do not produce solutions, difficulties in implementing online-based work policies due to uneven technological progress in each region, increasing COVID-19 cases, and the pile-up task of improving public service delivery. Current pandemic situations in Indonesia; an increasing number of COVID-19 cases in Indonesia with a total of 93,657 on July, 23rd 2020; The government-issued social distancing policies, physical distancing, work from home and PSBB to break the chain of COVID-19; Conducting community intelligence through online and offline COVID-19 prevention education; Java island as the most populated area in Indonesia (SUPAS 2015) experienced a prolonged red zone until the implementation of the PSBB; it's affected the economic turnover. The Impact of the COVID-19 Pandemic on Public Service Delivery; Limited access for providing community services; Issued a new policy; Closure of schools, markets, public facilities, restrictions on transportation passengers, and others; Providing online-based services. The conclusions and suggestions in this study are the application and development of the E-Government system; Creating new reliable policy standards; Employee training regarding online-based work systems; Efforts to distribute technology and information to every remote area in Indonesia